ANALISIS PEMAKAIAN BAHASA PADA IKLAN PRODUK MINUMAN DI TELEVISI - Septia Uswatun Hasanah (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
This study aims to describe the use of language in advertising beverage products on television. The method used in this research is descriptive qualitative. The implementation of research refers to the design of language analysis techniques, namely the provision, analysis and presentation of data. The data is provided using the interview method and note taking technique. The results of the study found that in general the use of language in advertisements uses speech acts that state something (locution), provide information that interests the public (localization) which impacts to encourage them to use the advertised product. In addition, advertising also utilizes the implicative speech by packaging information presentations that implicitly invites people to buy or use the product.